A study on medication adherence, medication related challenges faced and coping strategies adopted by visually impaired subjects in a tertiary care hospital - R., Apoorva; Vasundara, K.; R. S., Umadevi (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Visual impairment poses a significant threat to proper medication practice leading to medication related challenges and some adopted self coping strategies with substantial impact on medication adherence. Visually impaired are potentially more likely to have unsafe medicine related practice which by itself is more rampant in general population. Studies related to them are largely unexplored and can provide data to improve disease management and health related quality of life. Objectives was to study the level of medication adherence, medication related challenges and self adopted coping strategies in visually impaired people. Methods: A cross sectional descriptive study enrolling 204 subjects with VI was done. Medication adherence was assessed using MMAS. Medication related challenges and self-adopted coping strategies was assessed by using pre-validated semi-structured questionnaire. Results: Majority of the subjects showed medium medication adherence with forgetfulness to take medicine as the main reason for non adherence. Difficulty in remembering the instructions, spilling of liquid medicine, taking wrong dose, difficulty in using topical medications were the most common challenges faced by them in daily drug administration. To overcome challenges locating the drugs at different places, finger felt volume for liquid medication, textural feeling of the drug or container, time tracking were the major self adopted coping strategies by the visually impaired subjects. Conclusions: Creating awareness of the medication related problem faced by visually impaired helps to provide adequate assistance to medication use and improve proper health care services in them.